In vitro Antiinflammatory Study of Poly(vinyl alcohol)/Hydroxyapatite Nanocomposites: Synthesis and Characterization - Dhanalakshmi, C.P.; Vijayalakshmi, L.; Narayanan, V. (Asian Journal of Chemistry, 2012)
Poly(vinyl alcohol)/hydroxyapatite nanocomposites of varying composition for biomaterial applications have been synthesized and characterized by XRD, FTIR, 31P NMR, TGA, DTA and FESEM. Hydroxyapatite nano rod embedded composite was prepared using poly(vinyl alcohol) as a matrix with different weight percentages. The results indicated that the size and crystallinity of hydroxyapatite nano particles decreases with increase in poly(vinyl alcohol) concentration in the composite. SEM confirms the presence of hydroxyapatite nano rod crystals in poly(vinyl alcohol) matrix. Poly(vinyl alcohol)/hydroxyapatite nano composites were screened for antimicrobial activity.